2017
DOI: 10.4172/2324-8785.1000312
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in FullField Thickness Measurements of the Human Eardrum

Abstract: Recently, we published several full-field human tympanic membrane data sets that were obtained using a modified high-resolution optical coherence tomography setup 1 . In this short communication letter, we provide an overview of the active research fields in which these data have been used or in which human tympanic membrane thickness measurements play an instrumental role. These applications include finite element modeling of the middle ear system, medical diagnosis of middle ear pathology and the design of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Thus, OCT can be beneficially utilized for visualizing the middle ear morphology and it allows the spatially resolved measurement of the tympanic membrane thickness. 2,3 Other studies have demonstrated that OCT can be used for imaging cholesteatoma 4 and tympanosclerosis. 5 In middle ear surgery, OCT has been utilized for the assessment of ossicles and middle ear prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, OCT can be beneficially utilized for visualizing the middle ear morphology and it allows the spatially resolved measurement of the tympanic membrane thickness. 2,3 Other studies have demonstrated that OCT can be used for imaging cholesteatoma 4 and tympanosclerosis. 5 In middle ear surgery, OCT has been utilized for the assessment of ossicles and middle ear prostheses.…”
Section: Introductionmentioning
confidence: 99%